Construction Method of Tooth Profile of a Parallel Shaft Circular Cross Section Line Gear - He Enyi (Jixie chuandong)
Based on the space curve meshing theory,the transmission mechanism of parallel shaft line gear is studied. Taking the spiral line as the center line,the surface equation is studied as the cross section is circle,and the driving surface is constructed according to the equation. The driven surface is constructed according to the driven center line and the same circular section of the driving surface. The forward and reverse contact lines on the driving surface are analyzed,and the contact line of the driven gear is obtained according to the space curve meshing equation. The forward and reverse contact line should meet the driven surface which is constructed by the construction method as the driving surface is constructed. The method by increasing the number of teeth to improve its coincidence degree to increase transmission stability is studied. The kinematics simulation experiment is carried out by the established 3 D line gear model. The results show the parallel shaft circular section line gear constructed by this method can be assembled without normal gap,and there is no interference during the transmission process and it can meet the designed transmission ratio.